SLEEP QUALITY AND MENTAL HEALTH IN MEDICAL STUDENTS (CIPEEX, 2025)
Poor sleep quality is a frequent yet underestimated determinant of mental health among medical students worldwide. Growing evidence indicates that irregular schedules, heavy workloads, and high stress levels during medical training contribute to insomnia, daytime sleepiness, and mood disturbances. This study aimed to synthesize recent findings on the prevalence, correlates, and consequences of sleep disturbances among medical students. An integrative review was conducted using five peer-reviewed studies indexed in PubMed (Vidović et al., 2025; Valladares-Garrido et al., 2025; Almalki et al., 2025; Vasava et al., 2025; Tran et al., 2023). These studies, performed in diverse geographic settings, assessed sleep quality mainly through the Pittsburgh Sleep Quality Index (PSQI) and related it to mental health indicators such as depression, anxiety, stress, and academic performance. Across the studies, between one-third and three-quarters of medical students reported poor sleep quality, with particularly high rates in preclinical years and in female students. Insomnia and delayed sleep onset were consistently associated with higher odds of anxiety, depressive symptoms, and stress (odds ratios ranging from 2.5 to 3.5), as well as reduced life satisfaction and impaired academic performance. Factors such as excessive screen time, high perceived stress, and inadequate coping strategies emerged as important contributors to sleep problems. The converging evidence highlights a global and multifactorial burden of sleep disturbances in medical education. These findings underscore the need for institutional strategies to promote sleep hygiene and mental well-being, including stress management programs, early screening for insomnia, and curricular adjustments to reduce sleep deprivation. Addressing sleep quality as a modifiable risk factor may improve not only the mental health but also the academic success of future physicians.